2021
DOI: 10.1038/s41598-021-88977-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of fluoroquinolone resistance and possible mechanisms in clinical isolates of Stenotrophomonas maltophilia from Iran

Abstract: Stenotrophomonas maltophilia exhibits wide spectrum of fluoroquinolone resistance using different mechanisms as multidrug efflux pumps and Smqnr alleles. Here, the role of smeDEF, smeVWX efflux genes and contribution of Smqnr alleles in the development of fluoroquinolone resistance was assessed. Ciprofloxacin, levofloxacin and moxifloxacin resistance were found in 10.9%, 3.5%, and 1.6% of isolates, respectively. More than four-fold differences in ciprofloxacin MICs were detected in the presence of reserpine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…However, resistance development has never slowed, warranting suitable sensitizers. 111 Previous research has reported highlevel fluoroquinolone resistance of Shigella dysenteriae induced by a PMF-dependent efflux system. 112 Several fluoroquinolone adjuvants are found to influence ΔΨ or ΔpH.…”
Section: Pmf-modulating Compounds Resensitize Other Antibiotic Classesmentioning
confidence: 99%
“…However, resistance development has never slowed, warranting suitable sensitizers. 111 Previous research has reported highlevel fluoroquinolone resistance of Shigella dysenteriae induced by a PMF-dependent efflux system. 112 Several fluoroquinolone adjuvants are found to influence ΔΨ or ΔpH.…”
Section: Pmf-modulating Compounds Resensitize Other Antibiotic Classesmentioning
confidence: 99%
“…strain I6 showed high similarity (identity ≥ 99.88%) with Stenotrophomonas maltophilia. This species is increasingly reported as an opportunistic and nosocomial pathogens (Alsuhaibani et al 2021 ) and it shows resistance to different antibiotics such as carbapenems and fluoroquinolone (Harmon et al 2019 ; Azimi et al 2021 ; Bostanghadiri et al 2021 ). Results of BLAST and RDP analyses were confirmed by the Bayesian and ML phylogenetic analyses inferred on the basis of the obtained 16S rRNA gene sequences (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the last 10 years, an increase in the number of isolates resistant to this chemotherapeutic agent has been observed in various regions of the world [ 28 , 32 ]. The second commonly used group of drugs in the treatment of infections caused by S. maltophilia strains are the fluoroquinolones, mainly levofloxacin [ 28 , 33 , 34 ]. Despite the high cure rates of S. maltophilia infections with levofloxacin monotherapy, a trend towards the selection of resistance to this fluoroquinolone has been observed [ 33 ].…”
Section: Discussionmentioning
confidence: 99%